Larval instars determination and secondary production of the mayfly Baetis idei (Ephemeroptera: Baetidae) from rivers in the Bukit Merah catchment area, Perak - Siti Hamidah I.,; Suhaila A.H.,; Nur Aida H., (Penerbit Universiti Kebangsaan Malaysia, 2017)
The study of an insect’s life cycle is important to understand the abundance, diversity, development and the environment in which it lives. To date, only limited investigations have been conducted in Malaysia on the mayfly Baetis, a genus of ephemeropterans. Here, we report a study on the larval instar determination and secondary production of Baetis idei in four rivers in the Bukit Merah catchment area, Perak. Samples were collected monthly from May 2014 until April 2015 using the kick-net and drag methods. B. idei displayed nine instar stages on a discriminant function analysis (DFA) scatter plot. Based on an analysis of nymphal body length and the emergence time of early and final larva instar, B. idei was found to be multivoltine in the Ara, the Jelai, Kurau and Ayer Itam rivers. The estimated annual production of B. idei in the four rivers ranged from -3.64 mg m-2 y-1 to 15.35 mg m-2 y-1 and the annual P/B ratio varied from -2.14 to 1.56. The highest turnover ratio for this species was recorded in Ara River. Different types of habitat and substrate at each river determined the abundance, voltinism, and secondary production of B. idei in the four rivers.